Efektivitas Layanan Konseling Kelompok dengan Teknik Behavior Contract untuk Mengatasi Perilaku Membolos Siswa di SMP Negeri 5 Tenggarong - Ericha Adevita Sambolayuk; Nuril Hidayanti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Truancy is a behavior that violates social norms and can occur when students leave school without proper reason, without permission, and during class hours. The impacts that occur are students become lazy individuals, students fall into bad relationships, low achievement, and poor understanding of the material. This study aims to determine the effectiveness of counseling services with the behavior contract technique to overcome truancy behavior of students at SMP Negeri 5 Tenggarong. This type of research is an experiment with a pre-experimental design using a one group pretest and posttest model. The study population is all 80 students of grade IX. The sample in this study consisted of 5 students identified as having truancy behavior. This relatively small sample size is a limitation of the study, so the results of the study are not intended to be generalized widely, but rather focus on an in-depth understanding of the case studied. The sampling technique used is non-probability sampling with a purposive sampling technique. This group counseling service was conducted 6 times using the behavior contract technique. The results of the study showed that the t-test showed a significant difference between the pretest and posttest. The average pretest score of 79.4 increased to 101.8 in the posttest, indicating an improvement in efforts to address student truancy. Based on these results, counseling services using the behavior contract technique were found to be effective in addressing student truancy.